Managing Neonatal Pulmonary Hypertension in Low‐Resource Settings - R. Kishore Kumar; Ju‐Lee Oei; Rajeshwari Madappa; Satyan Lakshminrusimha (Journal of Paediatrics and Child Health, 2026)
ABSTRACT Persistent pulmonary hypertension of the newborn (PPHN) is a critical condition marked by elevated pulmonary vascular resistance (PVR) and persistent hypoxemia, due to the failure of transition from foetal to neonatal circulation. Management focuses on reducing PVR, enhancing pulmonary vasodilation, and ensuring adequate oxygen delivery. Inhaled nitric oxide (iNO), an FDA‐approved therapy, effectively lowers PVR and improves oxygenation in term neonates. However, in resource‐limited settings, its use is constrained by high costs, the need for specialized equipment, and limited availability of medical‐grade iNO, with industrial‐grade NO sometimes used despite potential impurities. These limitations have led to increased use of accessible alternatives such as sildenafil, milrinone and other vasodilators, which offer vital options where iNO is not feasible. This review highlights regional variability in management, the impact of resource constraints, and the need for equitable care. Using India as an example, a 10‐step approach for managing PPHN in low‐resource settings is proposed, alongside a call for standardized protocols and further research into both established and emerging therapies.